The effect of conversion rate on prey-predator model with disease in prey using one- parameter bifurcation analysis / Alia Nur Izzah Zulkifli, Nurnaimi Yahya and Nur Nabila Sofea Mat Zizi - Zulkifli, Alia Nur Izzah; Yahya, Nurnaimi; Mat Zizi, Nur Nabila Sofea (2022)
This project offers a new method to investigate the effect of conversion rate on preypredator models with disease in prey using one-parameter bifurcation analysis. As we all know, prey and predator have a symbiotic relationship. Thus, knowing the stability of their population is crucial when parasite infection in prey populations is a serious issue that must not be neglected. In this project, we examine the stability analysis of the prey-predator model with the presence of disease in the prey population and to analyze the effects of the conversion rate of the prey-predator population, by using one-parameter bifurcation analysis. A few graphs of bifurcation, phase plane, and time series are plotted using mathematical software such as XPPAUT, Maple, and MATLAB. As the parameter value of the steady states grows, the system’s stability will change from stable to unstable or vice versa. According to our findings, the conversion rates effect can induce a switch in stability. As the conversion rate increases, the steady state of susceptible and infected prey are shifted from stable to unstable. We may conclude that the density of susceptible predator species reduces significantly, indicating that infected prey has a significant impact on the predator population.